![1.\\1)\;(p+8)^2=p^2+16p+64\\2)\;(10x-3y)^2=100x^2-60xy+9y^2\\3)\;(x-9)(x+9)=x^2-81\\(4m+7n)(7n-4m)=49n^2-16m^2\\\\2.\\1)\;16-c^2=(4-c)(4+c)\\2)\;p^2+2p+1=(p+1)^2\\3)\;9m^2-25=(3m-5)(3m+5)\\4)\;36m^2+24mn+4n^2=(6m+2n)^2\\\\3.\;(a-10)^2-(a-5)(a+5)=a^2-20a+100-(a^2-25)=\\=a^2-20a+100-a^2+25=125-20a 1.\\1)\;(p+8)^2=p^2+16p+64\\2)\;(10x-3y)^2=100x^2-60xy+9y^2\\3)\;(x-9)(x+9)=x^2-81\\(4m+7n)(7n-4m)=49n^2-16m^2\\\\2.\\1)\;16-c^2=(4-c)(4+c)\\2)\;p^2+2p+1=(p+1)^2\\3)\;9m^2-25=(3m-5)(3m+5)\\4)\;36m^2+24mn+4n^2=(6m+2n)^2\\\\3.\;(a-10)^2-(a-5)(a+5)=a^2-20a+100-(a^2-25)=\\=a^2-20a+100-a^2+25=125-20a](https://tex.z-dn.net/?f=1.%5C%5C1%29%5C%3B%28p%2B8%29%5E2%3Dp%5E2%2B16p%2B64%5C%5C2%29%5C%3B%2810x-3y%29%5E2%3D100x%5E2-60xy%2B9y%5E2%5C%5C3%29%5C%3B%28x-9%29%28x%2B9%29%3Dx%5E2-81%5C%5C%284m%2B7n%29%287n-4m%29%3D49n%5E2-16m%5E2%5C%5C%5C%5C2.%5C%5C1%29%5C%3B16-c%5E2%3D%284-c%29%284%2Bc%29%5C%5C2%29%5C%3Bp%5E2%2B2p%2B1%3D%28p%2B1%29%5E2%5C%5C3%29%5C%3B9m%5E2-25%3D%283m-5%29%283m%2B5%29%5C%5C4%29%5C%3B36m%5E2%2B24mn%2B4n%5E2%3D%286m%2B2n%29%5E2%5C%5C%5C%5C3.%5C%3B%28a-10%29%5E2-%28a-5%29%28a%2B5%29%3Da%5E2-20a%2B100-%28a%5E2-25%29%3D%5C%5C%3Da%5E2-20a%2B100-a%5E2%2B25%3D125-20a)
0\;npu\;Bcex\;x\\\\6.\;(2-x)(2+x)(4+x^2)+(6-x)^2=(4-x^2)(4+x^2)+36-12x+x^2=\\=16-x^4+36-12x+x^2=-x^4+x^2-12x+52" alt="4.\;(2x-7)(x+1)+3(4x-1)(4x+1)=2(5x-2)^2-53\\2x^2-5x-7+3(16x^2-1)=2(25x^2-20x+4)-53\\2x^2-5x-7+48x^2-3=50x^2-40x+8-53\\50x^2-5x-10=50x^2-40x-45\\35x=-35\\x=-1\\\\5.\;x^2-18x+84=(x^2-18x+81)+3=(x-9)^2+3>0\;npu\;Bcex\;x\\\\6.\;(2-x)(2+x)(4+x^2)+(6-x)^2=(4-x^2)(4+x^2)+36-12x+x^2=\\=16-x^4+36-12x+x^2=-x^4+x^2-12x+52" align="absmiddle" class="latex-formula">